Land use change and agricultural intensification: Key research questions and innovative approaches - Wu, JunJie; Li, Man (International Food Policy Research Institute, 2014)
This paper reviews land use modeling approaches for assessing the economic and environmental impacts of agri-cultural intensification. It discusses the theoretical foundations of the modeling approaches, describes how to parameterize such models when micro-level data are available, and examines how to integrate them with bio-physical models for policy evaluation. Based on the literature review, the paper identifies key research questions and discusses appropriate methods and data and promising areas for investigating those questions.